Prognostic factors and development of the practical prediction score for 7-day mortality of palliative patients in the emergency department - Torntarn Charascharungkiat; Welawat Tienpratarn; Chaiyaporn Yuksen; Chalermpon Bumrungsiri; Natthakorn Pongsettakul; Thidathit Prachanukool (Scientific Reports)
Abstract Background End-of-life (EOL) care aims to facilitate good death and fulfill the patient’s final desires. Despite the known benefits of palliative consultations, emergency physicians encounter challenges in decision-making due to limited palliative resources. Previous studies primarily focus on non-emergency settings; thus, we aimed to develop a practical prediction score for 7-day mortality for palliative patients in the emergency department (ED). Methods This retrospective cohort study, conducted at a tertiary-level university hospital in Thailand between June 2022 and May 2023, evaluated adult palliative patients who declined life-sustaining treatments. Variables associated with 7-day mortality were analyzed using univariable and multivariable logistic regression. Results Of 499 ED visits, 152 patients (30.46%) died within seven days. Six predictors were identified: solid malignancy, respiratory with mandibular movement, systolic blood pressure < 100 mmHg, lymphopenia, thrombocytopenia, and a blood urea nitrogen to creatinine ratio > 20. These factors were used to develop the Ramathibodi End-of-life (RAMA-EOL) score, demonstrating an AuROC curve of 80.46% (95% CI: 76.15–84.77). Patients with a score ≥ 3 had a positive likelihood ratio of 2.92 (95% CI: 2.38–3.57) for 7-day mortality. Conclusion The RAMA-EOL score reliably predicts 7-day mortality in palliative ED patients, facilitating timely palliative care interventions for high-risk individuals.